Preparation method of flexible protection layer for lithium metal negative electrode protection

By growing the UiO-66 protective layer in situ on the surface of polymer fibers of lithium metal batteries, the problems of lithium dendrites growth and solid electrolyte interface layer instability are solved, and the longer cycle life and higher safety of lithium batteries are achieved.

CN119640588APending Publication Date: 2025-03-18SICHUAN CHENGKEGUO RENEWABLE ENERGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411806523.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Lithium metal batteries are prone to form dendrites during charging and discharging, resulting in battery short circuits and safety accidents. The interface layer of solid electrolyte is unstable and leads to lithium loss. The volume expansion during the cycle increases the battery impedance.

Method used

In situ growth technology is used to construct the UiO-66 protective layer on the surface of polymer fibers. Through the strong interaction between the functionalized polyarylether polymer and the UiO-66 central metal, a stable and uniform flexible protective layer is formed to inhibit the growth of lithium dendrites and relieve volume expansion.

Benefits of technology

It significantly improves the stability, mechanicality and uniformity of the protective layer, extends the cycle life of lithium batteries, reduces safety risks, and improves the energy density and use efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640588A_ABST
    Figure CN119640588A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a flexible protective layer for lithium metal negative electrode protection, and belongs to the technical field of lithium metal batteries, and the preparation method specifically comprises the following steps: taking a polyarylether high-molecular polymer with a functional group as a main body, introducing metal salt, and spinning to obtain a nanofiber membrane with uniformly distributed central metal ions; a UiO-66 series framework material is grown on the surface of the fiber in situ, so that a flexible protective layer with the UiO-66 series framework material uniformly distributed and stable is obtained. The excellent rigidity of a polyarylether high-molecular polymer is utilized, the flexibility of a protective layer is improved, functional groups are introduced, and strong chemical bonds or electrostatic interaction between the functional groups and central metal ions is utilized, so that the adhesive force in the nucleation and growth process of the UiO-66 series framework material is enhanced, and the performance of the UiO-66 series framework material is improved. When the material is used for lithium metal negative electrode protection, the stability of a solid electrolyte interface can be effectively improved, the cycle life of a lithium battery is prolonged, and the performance consistency of the lithium battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium metal batteries, and in particular relates to a method for preparing a flexible protective layer for protecting a lithium metal negative electrode. Background Art

[0002] Lithium metal batteries have important research value and application potential in the field of battery technology because of their extremely high theoretical specific capacity (3860mAh / g) and the lowest negative potential (-3.04V, compared with the standard hydrogen electrode). However, lithium metal batteries face many technical challenges in practical applications, especially in the use of lithium metal anodes. The most common problems of lithium metal anodes can be summarized as follows: First, dendrites are easily formed during the charging and discharging process. These dendrites will not only pierce the diaphragm, causing battery short circuits, but even cause thermal runaway and safety accidents in severe cases. The growth of lithium dendrites not only reduces the cycle life of the battery, but also greatly increases the safety risk of the battery. Second, the unstable solid electrolyte interface layer (SEI) causes lithium metal to be continuously exposed to the electrolyte, resulting in irreversible lithium loss caused by the side reaction between the electrolyte and lithium, reducing the coulombic efficiency and cycle life of the battery. Third, the volume expansion during the cycle process continuously increases the battery impedance, hindering the development of battery technology. In addition, the accelerated growth of lithium dendrites at high current density will further aggravate the above problems.

[0003] To solve the above problems, researchers have proposed a variety of methods to protect lithium metal anodes, including introducing an artificial protective layer on the surface of lithium metal to inhibit the growth of lithium dendrites and reduce the direct contact between lithium metal and electrolyte, thereby improving the cycle stability and safety of the battery. However, traditional protective layer materials usually have problems such as insufficient mechanical properties, poor conductivity and poor compatibility with lithium metal, which are difficult to meet the needs of practical applications. For example, an alloy layer containing a lithium phase is constructed on the surface of lithium metal, but it is difficult to control the thickness. When constructing the halide component, fluoride is difficult to dissolve in conventional solvents, making it difficult to prepare the protective layer (Afluorinated alloy-type interfacial layer enabled by metal fluoridenanoparticle modification for stabilizing Li metal anodes). The inorganic composite protective layer obtained by deposition has poor mechanical properties and shows poor resistance to lithium dendrite growth and volume expansion (AnIn Situ Generated Organic / Inorganic Hybrid SEI Layer Enables Li Metal Anodeswith Dendrite Suppression Ability, High-Rate Capability, and Long-Life Stability).

[0004] In order to overcome the shortcomings of traditional materials, the development of flexible, durable and lithium metal compatible protective layers has become a research hotspot. The protective layer needs to have a certain degree of flexibility to adapt to the volume change of lithium metal during charging and discharging, avoid rupture caused by stress concentration, and also have good ionic conductivity to ensure the normal operation of the battery. Since Professor Ostermann first combined the metal-organic framework (MOF) material ZIF-8 with polyvinyl pyrrolidone nanofiber membrane in 2011, MOF has shown significant application prospects in flexible protective layers due to its unique structural advantages. Specifically, MOF has an adjustable porous structure and high specific surface area through strong chemical bonds between central metal ions and organic ligands, providing a large number of ion transport channels. Among them, UiO-66 is considered to be an ideal material for SEI because of its unique metal-organic framework structure, which exhibits excellent lithium ion transport efficiency and excellent insulation. However, UiO-66 is traditionally added directly to polymers in powder form, which limits its effective utilization and reduces the overall performance of the material. For example, in a recent work by Professor Zhang Jianguo of Beijing Institute of Technology (In situ bridging soft polymer and robust metal-organic frameworks as electrolyte for long-cycling solid-state potassium-organic batteries), the direct addition of UiO-66 into a soft polymer would mask the internal pores of the MOF particles, significantly reducing the number of exposed active sites and reducing MOF stability, limiting the availability and activity of MOF in applications. Summary of the invention

[0005] In view of the problems existing in the application of UiO-66 in the lithium metal negative electrode protection layer, the present invention provides a method for preparing a flexible protective layer for lithium metal negative electrode protection, and constructs a UiO-66 protective layer on the surface of a polymer fiber by utilizing an in-situ growth technology. The strong interaction between the functionalized polyarylether polymer substrate and the UiO-66 central metal significantly improves the stability, mechanical properties and uniformity of the protective layer, thereby inhibiting the growth of lithium dendrites and alleviating volume expansion.

[0006] In order to achieve the above purpose, the technical method adopted by the present invention is as follows:

[0007] A method for preparing a flexible protective layer for lithium metal negative electrode protection comprises the following steps:

[0008] Step 1, preparing a polyarylether polymer having at least one functional group, wherein the functional group is a nitrile group, a hydroxyl group, a carboxyl group, a sulfonic acid group, an amino group or a thiol group;

[0009] Step 2, dissolving the metal salt in an organic solvent, adding the polyarylether polymer obtained in step 1, stirring and dissolving at 30-60° C. for 12-24 hours, and obtaining a precursor spinning solution with a mass fraction of 15%-25%; wherein the mass ratio of the metal salt to the polyarylether polymer is 0.01-0.2:1;

[0010] Step 3, spinning the precursor spinning solution into a nanofiber membrane through an electrospinning process;

[0011] Step 4, immersing the nanofiber membrane in an alcohol solvent, adding an excess of acidic catalyst and organic ligand raw materials to fully infiltrate, placing the resulting mixed liquid in a high-pressure reactor, and heat treating at 120-160° C. for 24-48 hours to obtain a nanofiber membrane with a UiO-66 series framework grown thereon;

[0012] Step 5: Wash the obtained nanofiber membrane grown with the UiO-66 series framework to neutrality, and dry it to obtain a flexible protective layer for protecting the lithium metal negative electrode.

[0013] Furthermore, the specific preparation process of step 1 is:

[0014] Step 1.1, adding bisphenol monomer (BP), dihalobenzonitrile and alkaline catalyst in a molar ratio of 1:1.1-1.5:1.1-2 to a mixed solvent of toluene and N-methylpyrrolidone (NMP), with a solid-liquid ratio of 1:4, slowly heating to 120° C.-140° C., dehydrating for 1-2 hours, to obtain a mixed solution;

[0015] Step 1.2, gradually heating the mixed solution to 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, and 180°C at a rate of 5-10°C per 10 minutes, and maintaining each temperature for 1-2 hours until the viscosity of the system no longer increases, thereby obtaining a crude polymer;

[0016] Step 1.3, adding the crude polymer to anhydrous ethanol for solidification for 12 to 24 hours, crushing to obtain a crude product, and subjecting it to multiple purification treatments to obtain a polyarylether polymer having at least one functional group.

[0017] Furthermore, the purification process described in step 1.3 is: first washing to neutrality to remove residual alkaline catalyst, drying, and then refluxing to remove bisphenol monomers, dihalobenzonitrile and small molecule oligomers that are not involved in the polymerization, and drying again, and dissolving in NMP solution; the last purification treatment does not need to be dissolved in NMP solution.

[0018] Furthermore, the bisphenol monomer in step 1.1 is one or a mixture of bisphenol A of different configurations, bisphenol S, phthaloline, potassium hydroquinone sulfonate, phthalazinone biphenyl, and diphenol bisphenols; the dihalobenzonitrile is dichlorobenzonitrile or difluorobenzonitrile; and the alkaline catalyst is sodium carbonate, potassium carbonate, or lithium carbonate.

[0019] Furthermore, in step 1.1, the volume ratio of toluene to NMP is 3:1.

[0020] Furthermore, the metal ion contained in the metal salt in step 2 is Zr 4+ 、Zn 2+ 、Co 3+ or Fe 3+ .

[0021] Furthermore, the organic solvent in step 2 is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and chloroform.

[0022] Furthermore, the specific process of electrospinning in step 3 is as follows: under the conditions of ambient temperature of 30±5°C and humidity of 40-60%, a 24-gauge needle and a 5mL syringe are used, a metal roller with a rotation speed of 200rpm is set as a receiver, the receiver is 15cm away from the needle tip, the booster speed is 0.01-0.1mL / min, 16kV positive high voltage and -2kV negative high voltage are applied, and spinning is continued for 10-12 hours.

[0023] Furthermore, the alcohol solvent in step 4 is a mixture of one or more of ethylene glycol, isopropanol or anhydrous ethanol.

[0024] Furthermore, the acidic catalyst in step 4 is trifluoroacetic acid (TFA), acetic acid or nitric acid.

[0025] Furthermore, the organic ligand raw material in step 4 is terephthalic acid (BDC), 2-aminoterephthalic acid (NH2-BCD) or 2-nitroterephthalic acid (NO2-BCD).

[0026] Furthermore, when the organic ligand raw material is terephthalic acid, a UiO-66 framework material is grown; when the organic ligand raw material is 2-aminoterephthalic acid, a NH2-UiO-66 framework material is grown; when the organic ligand raw material is 2-nitroterephthalic acid, a NO2-UiO-66 framework material is grown.

[0027] Furthermore, in step 4, the volume ratio of the acidic catalyst to the alcohol solvent is 1:3-5, and the mass ratio of the nanofiber membrane to the organic ligand raw material is 1:8-16.

[0028] Furthermore, in step 5, the washing solvent is anhydrous ethanol and deionized water, the drying temperature is 40 to 60° C., and the drying time is 24 to 48 hours.

[0029] A composite lithium metal is obtained by rolling the flexible protective layer on the surface of the lithium metal, wherein the thickness of the flexible protective layer is 5 to 40 μm.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The present invention proposes a method for preparing a flexible protective layer for lithium metal negative electrode protection, which takes a polyarylether polymer with functional groups as the main body, introduces metal salts, and spins to obtain a nanofiber membrane with uniform distribution of central metal ions, and in situ grows UiO-66 series framework materials on the fiber surface to obtain a flexible protective layer with uniform and stable distribution of UiO-66 series framework materials;

[0032] 2. Specifically, the present invention adopts a polyarylether polymer having a functional group as the main body. On the one hand, the excellent rigidity of the polyarylether polymer is utilized to improve the flexibility of the protective layer; on the other hand, functional groups such as nitrile, hydroxyl, carboxyl, sulfonic acid, amino or thiol are introduced to utilize the strong chemical bond (metal coordination or hydrogen bond interaction) or electrostatic interaction formed between the functional groups and the central metal ion to enhance the adhesion during the nucleation and growth of the UiO-66 series framework material. It is only necessary to add metal salts when configuring the precursor spinning solution, and there is no need to add metal salts for the second time during in-situ growth, so that the UiO-66 series framework material can grow uniformly and stably. While retaining the porous structure, high specific surface area and excellent conductivity of the UiO-66 series framework material, it is ensured that the UiO-66 series framework material is not easy to fall off during the battery cycle.

[0033] 3. When the present invention is used for lithium metal negative electrode protection, it can effectively improve the stability of the solid electrolyte interface, reduce the brittleness and instability of the SEI layer, thereby improving the cycle life and performance consistency of the lithium battery, and ensuring the reliability of the battery during multiple charge and discharge processes; at the same time, it inhibits the growth of lithium dendrites, reduces the risk of short circuits, and reduces the volume expansion effect of lithium metal during the charge and discharge process, thereby improving the energy density and utilization efficiency of lithium batteries and promoting the practical application of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 The SEM (scanning electron microscope) images of the PEN-Li composite nanofiber layer obtained in Comparative Example 1 and the PEN@UiO-66-Li composite nanofiber layer obtained in Example 2; wherein (a) is Comparative Example 1; (b) is Example 2;

[0036] Figure 2 Infrared spectra of UiO-66 before and after growth on PEN;

[0037] Figure 3 The charge-discharge curves of the PEN-Li composite nanofiber layer obtained in Comparative Example 1 and the PEN@UiO-66-Li composite nanofiber layer obtained in Example 2 in a PEN@UiO-66-Cu‖S full battery at 100 cycles;

[0038] Figure 4 This is a graph showing the lithium deposition and stripping efficiency of the PEN@UiO-66-Cu composite nanofiber layer obtained in Example 2 in a Li‖PEN@UiO-66-Cu half-cell;

[0039] Figure 5 This is a lithium deposition and stripping curve of the PEN@UiO-66-Cu composite nanofiber layer obtained in Example 2 at different numbers of cycles in the Li‖PEN@UiO-66-Cu half-cell. DETAILED DESCRIPTION

[0040] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with the examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. All raw materials of the present invention are not particularly limited in their sources, and can be purchased on the market or prepared according to conventional methods well known to those skilled in the art.

[0041] Example 1

[0042] This embodiment prepares a polyarylether polymer having a nitrile functional group, which specifically includes the following steps:

[0043] Step 1, bisphenol A, dichlorobenzonitrile and potassium carbonate were mixed in a three-necked flask in a molar ratio of 1:1.5:1.6, placed in a mixed solution of toluene and NMP in a volume ratio of 3:1, wherein the solid-liquid ratio was 1:4, slowly heated to 120° C., and dehydrated for 12 hours to obtain a mixed solution;

[0044] Step 2, gradually heating the mixed solution to 145° C., 150° C., 155° C., 160° C., 165° C., 170° C., 175° C., and 180° C. at a rate of 5° C. per 10 min, and maintaining each temperature for 1.5 h until the viscosity of the system no longer increases, thereby obtaining a crude polymer;

[0045] Step 3, adding the crude polymer to anhydrous ethanol for solidification for 16 hours, crushing to obtain a crude product, and subjecting it to multiple purification treatments to obtain a polyarylether polymer having a nitrile group (denoted as PEN); wherein the purification process is: first washing with deionized water to neutrality to remove residual alkaline catalyst, drying, and then refluxing with anhydrous ethanol to remove bisphenol monomers, dihalobenzonitrile and small molecular oligomers (such as dimers, tetramers, etc.) that are not involved in the polymerization, and drying again, and dissolving in an NMP solution; the last purification treatment does not need to be dissolved in an NMP solution.

[0046] Example 2

[0047] Based on the polyarylether polymer having nitrile groups obtained in Example 1, this example prepares a flexible protective layer for lithium metal negative electrode protection, which specifically includes the following steps:

[0048] Step 1, dissolving ZrCl4 metal salt in N,N-dimethylformamide at a concentration of 0.01M, adding the polyarylether polymer having a nitrile group obtained in Example 1, stirring and dissolving at 60°C for 24 hours, and obtaining a precursor spinning solution with a mass fraction of 18%;

[0049] Step 2: Spin the precursor spinning solution into a nanofiber membrane through an electrospinning process. The specific process is as follows:

[0050] Under the conditions of ambient temperature of 30±5℃ and humidity of 50%, a 24-gauge needle and a 5mL syringe were used, a metal drum with a rotation speed of 200rpm was set as the receiver, the receiver was 15cm away from the needle tip, the booster speed was 0.018mL / min, 16kV positive high voltage and -2kV negative high voltage were applied, and spinning continued for 10h;

[0051] Step 3, 0.1 g of the nanofiber membrane was immersed in 50 mL of a mixed solution of ethylene glycol and trifluoroacetic acid, wherein the volume ratio of ethylene glycol to trifluoroacetic acid in the mixed solution was 3:1, and used as a ligand solution, and finally terephthalic acid (1.0016 g or 6 mmol) was added. After sufficient ultrasonic infiltration, the obtained mixed liquid was placed in a high pressure reactor and heat treated at 120 ° C for 24 h to obtain a nanofiber membrane with UiO-66 grown thereon;

[0052] Step 4, washing the obtained nanofiber membrane grown with UiO-66 with anhydrous ethanol and deionized water until neutral, treating in a vacuum oven at 60° C. for 24 h, and obtaining a flexible protective layer for lithium metal negative electrode protection, which is recorded as PEN@UiO-66 fiber membrane;

[0053] Step 5: Roll the PEN@UiO-66 fiber membrane onto the surface of lithium metal to obtain an integrated composite fiber / lithium electrode, recorded as PEN@UiO-66-Li composite nanofiber layer; then roll the PEN@UiO-66 fiber membrane onto the surface of the copper current collector to obtain an integrated composite fiber / copper electrode, recorded as PEN@UiO-66-Cu composite nanofiber layer; the thickness of the PEN@UiO-66 fiber membrane is 22 μm.

[0054] Comparative Example 1

[0055] Based on the polyarylether polymer having a nitrile group obtained in Example 1, this comparative example prepared a flexible protective layer for lithium metal negative electrode protection, which specifically includes the following steps:

[0056] Step 1, dissolving the polyarylether polymer having a nitrile group obtained in Example 1 in N,N-dimethylformamide, adding, stirring and dissolving at 60° C. for 24 hours, to obtain a precursor spinning solution with a mass fraction of 18%;

[0057] Step 2: Spin the precursor spinning solution into a nanofiber membrane through an electrospinning process. The specific process is as follows:

[0058] Under the conditions of ambient temperature of 30±5℃ and humidity of 50%, a 24-gauge needle and a 5mL syringe were used, a metal drum with a rotation speed of 200rpm was set as the receiver, the receiver was 15cm away from the needle tip, the booster speed was 0.018mL / min, 12kV positive high voltage and -2kV negative high voltage were applied, and spinning continued for 10 hours;

[0059] Step 3, treating the nanofiber membrane in a vacuum oven at 60° C. for 24 h to obtain a flexible protective layer for lithium metal negative electrode protection, which is denoted as PEN fiber membrane;

[0060] Step 5: Roll the PEN fiber membrane onto the surface of lithium metal to obtain an integrated composite fiber / lithium electrode, which is referred to as a PEN-Li composite nanofiber layer. The thickness of the PEN fiber membrane is 15 μm.

[0061] Example 3

[0062] Based on the polyarylether polymer having nitrile groups obtained in Example 1, this example prepares a flexible protective layer for lithium metal negative electrode protection, which specifically includes the following steps:

[0063] Step 1, dissolving ZrCl4 metal salt in N,N-dimethylformamide at a concentration of 0.01M, adding the polyarylether polymer having a nitrile group obtained in Example 1, stirring and dissolving at 60°C for 24 hours, and obtaining a precursor spinning solution with a mass fraction of 18%;

[0064] Step 2: Spin the precursor spinning solution into a nanofiber membrane through an electrospinning process. The specific process is as follows:

[0065] Under the conditions of ambient temperature of 30±5℃ and humidity of 50%, a 24-gauge needle and a 5mL syringe were used, a metal drum with a rotation speed of 200rpm was set as the receiver, the receiver was 15cm away from the needle tip, the booster speed was 0.018mL / min, 16kV positive high voltage and -2kV negative high voltage were applied, and spinning continued for 10h;

[0066] Step 3, 0.1 g of the nanofiber membrane was immersed in 50 mL of a mixed solution of ethylene glycol and trifluoroacetic acid, wherein the volume ratio of ethylene glycol to trifluoroacetic acid in the mixed solution was 3:1, and used as a ligand solution. Finally, 2-aminoterephthalic acid (1.086 g or 6 mmol) was added. After sufficient ultrasonic infiltration, the obtained mixed liquid was placed in a high-pressure reactor and heat-treated at 120 ° C for 24 h to obtain a nanofiber membrane grown with NH2-UiO-66;

[0067] Step 4, washing the obtained nanofiber membrane grown with NH2-UiO-66 with anhydrous ethanol and deionized water until neutral, treating in a vacuum oven at 60°C for 24h, and obtaining a flexible protective layer for lithium metal negative electrode protection, which is recorded as PEN@NH2-UiO-66 fiber membrane;

[0068] Step 5: Roll the PEN@NH2-UiO-66 fiber membrane onto the surface of lithium metal to obtain an integrated composite fiber / lithium electrode, recorded as PEN@NH2-UiO-66-Li composite nanofiber layer. The thickness of the PEN@NH2-UiO-66 fiber membrane is 25 μm.

[0069] The PEN-Li composite nanofiber layer obtained in Comparative Example 1 and the PEN@UiO-66-Li composite nanofiber layer obtained in Example 2 were characterized and their performance tested.

[0070] The SEM test results of the PEN-Li composite nanofiber layer obtained in Comparative Example 1 and the PEN@UiO-66-Li composite nanofiber layer obtained in Example 2 are as follows: Figure 1 As shown, Figure 1 (a) is Comparative Example 1, and (b) is Example 2. It can be seen that the fiber morphology of the PEN-Li composite nanofiber layer and the PEN@UiO-66-Li composite nanofiber layer is uniform, without nodules and bead-like structures, but the fibers of the PEN@UiO-66-Li composite nanofiber layer are thicker, indicating that UiO-66 grows uniformly on the fiber surface.

[0071] Figure 2The infrared spectra of PEN before and after the growth of UiO-66 on PEN are the infrared spectra of the PEN obtained in Example 1 and the PEN@UiO-66 fiber membrane obtained in Example 2. It can be seen that after the growth of UiO-66, the PEN@UiO-66 polymer has a wavelength of 1650 cm -1 The stretching vibration peak of UiO-66 appeared at 2234 cm -1 The peak intensity increased, which was attributed to the interaction between the central metal ion and the nitrile group of the UiO-66 ligand, which strengthened the stretching vibration of the nitrile group.

[0072] The PEN-Li composite nanofiber layer obtained in Comparative Example 1 and the PEN@UiO-66-Li composite nanofiber layer obtained in Example 2 were used as negative electrodes, sulfur-carbon with a sulfur content of 64% was used as a positive electrode, a solution containing 1M LiTFSI and 1wt% LiNO3 as lithium salts, and a DME:DOL solution with a volume ratio of 1:1 was used as an electrolyte to assemble a PEN@UiO-66-Cu‖S full battery, which had a sulfur loading of 3mg / cm 2 The discharge curve at 100 cycles under 0.5C conditions is as follows: Figure 3 As shown, it can be seen that the capacity of the PEN@UiO-66-Cu‖S full battery assembled with PEN@UiO-66-Li is 1101 mAh / g at the 100th cycle, which is much higher than that of the PEN@UiO-66-Cu‖S full battery assembled with PEN-Li. This is attributed to the fact that the PEN@UiO-66-Li composite nanofiber layer forms a stable lithium metal interface layer during the cycle, inhibiting the generation of "dead lithium" and achieving efficient and uniform utilization of the lithium metal negative electrode.

[0073] The PEN@UiO-66-Cu composite nanofiber layer obtained in Example 2 was used as the negative electrode, and a Li|PEN@UiO-66-Cu half-cell was assembled with a lithium sheet to study the effect of the PEN@UiO-66-Cu composite nanofiber layer on lithium deposition. A solution containing 1 M LiTFSI and 1 wt % LiNO3 as lithium salt and a volume ratio of 1:1 DME:DOL was used as the electrolyte. 2 The deposition capacity and 1mA / cm 2 At a current density of , the lithium deposition and stripping efficiency of the Li‖PEN@UiO-66-Cu half-cell is as follows: Figure 4 As shown in Figure 2, it can be seen that the Li‖PEN@UiO-66-Cu half-cell can stably deposit and strip for more than 160 cycles. The lithium deposition and stripping curves of the Li‖PEN@UiO-66-Cu half-cell at different cycles are shown in Figure 2. Figure 5 As shown, it can be seen that 1 mAh of lithium can be stably stripped out after 160 cycles, and the lithium nucleation overpotential after 160 cycles is still 30 mV, which has good reversibility.

[0074] In summary, it is shown that a nanofiber membrane with uniform distribution of central metal ions is obtained by introducing metal salts with polyarylether polymers having functional groups as the main body and spinning. By in situ growing UiO-66 series framework materials on the fiber surface, a flexible protective layer with uniform distribution and stability of UiO-66 series framework materials can be obtained, which can be used for lithium metal negative electrode protection and can exhibit excellent lithium deposition and stripping efficiency and cycle stability.

[0075] The present invention uses specific examples to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enables any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A method for preparing a flexible protective layer for lithium metal negative electrode protection, characterized in that: The following steps are involved: Step 1, preparing a polyarylether polymer having at least one functional group, wherein the functional group is a nitrile group, a hydroxyl group, a carboxyl group, a sulfonic acid group, an amino group or a thiol group; Step 2, dissolving the metal salt in an organic solvent, adding the polyarylether polymer obtained in step 1, stirring and dissolving at 30-60° C. for 12-24 hours, and obtaining a precursor spinning solution with a mass fraction of 15%-25%; wherein the mass ratio of the metal salt to the polyarylether polymer is 0.01-0.2:1; Step 3, spinning the precursor spinning solution into a nanofiber membrane through an electrospinning process; Step 4, immersing the nanofiber membrane in an alcohol solvent, adding an excess of acidic catalyst and organic ligand raw materials to fully infiltrate, placing the resulting mixed liquid in a high-pressure reactor, and heat treating at 120-160° C. for 24-48 hours to obtain a nanofiber membrane with a UiO-66 series framework grown thereon; Step 5: Wash the obtained nanofiber membrane grown with the UiO-66 series framework to neutrality, and dry it to obtain a flexible protective layer for protecting the lithium metal negative electrode.

2. The method for preparing a flexible protective layer for lithium metal negative electrode protection according to claim 1, characterized in that: The specific preparation process of step 1 is: Step 1.1, adding bisphenol monomer, dihalobenzonitrile and alkaline catalyst in a molar ratio of 1:1.1-1.5:1.1-2 to a mixed solvent of toluene and N-methylpyrrolidone, with a solid-liquid ratio of 1:4, slowly heating to 120° C.-140° C., dehydrating for 1-2 hours, to obtain a mixed solution; Step 1.2, gradually heating the mixed solution to 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, and 180°C at a rate of 5-10°C per 10 minutes, and maintaining each temperature for 1-2 hours until the viscosity of the system no longer increases, thereby obtaining a crude polymer; Step 1.3, adding the crude polymer to anhydrous ethanol for solidification for 12 to 24 hours, crushing to obtain a crude product, and subjecting it to multiple purification treatments to obtain a polyarylether polymer having at least one functional group.

3. The method for preparing a flexible protective layer for lithium metal negative electrode protection according to claim 2, characterized in that: The purification process described in step 1.3 is: first wash to neutrality to remove residual alkaline catalyst, dry, and then reflux to remove bisphenol monomer, dihalobenzonitrile and small molecule oligomers that are not involved in the polymerization, dry again, and dissolve in NMP solution; the last purification treatment does not need to be dissolved in NMP solution.

4. The method for preparing a flexible protective layer for lithium metal negative electrode protection according to claim 2, characterized in that: The bisphenol monomer in step 1.1 is one or a mixture of bisphenol A of different configurations, bisphenol S, phthaloline, potassium hydroquinone sulfonate, phthalazinone biphenyl, and diphenol bisphenols; the dihalobenzonitrile is dichlorobenzonitrile or difluorobenzonitrile; and the alkaline catalyst is sodium carbonate, potassium carbonate, or lithium carbonate.

5. The method for preparing a flexible protective layer for lithium metal negative electrode protection according to claim 2, characterized in that: The volume ratio of toluene to NMP in step 1.1 is 3:

1.

6. The method for preparing a flexible protective layer for lithium metal negative electrode protection according to any one of claims 1 to 5, characterized in that: The metal ion contained in the metal salt in step 2 is Zr 4+ 、Zn 2+ 、Co 3+ or Fe 3+ .

7. The method for preparing a flexible protective layer for lithium metal negative electrode protection according to any one of claims 1 to 5, characterized in that: The organic solvent in step 2 is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and chloroform.

8. The method for preparing a flexible protective layer for lithium metal negative electrode protection according to any one of claims 1 to 5, characterized in that: In step 4, the alcohol solvent is a mixture of one or more of ethylene glycol, isopropanol or anhydrous ethanol, the acid catalyst is trifluoroacetic acid, acetic acid or nitric acid, and the organic ligand raw material is terephthalic acid, 2-aminoterephthalic acid or 2-nitroterephthalic acid.

9. The method for preparing a flexible protective layer for lithium metal negative electrode protection according to any one of claims 1 to 5, characterized in that: In step 4, the volume ratio of the acidic catalyst to the alcohol solvent is 1:3-5, and the mass ratio of the nanofiber membrane to the organic ligand raw material is 1:8-16.

10. The method for preparing a flexible protective layer for lithium metal negative electrode protection according to any one of claims 1 to 5, characterized in that: The washing solvents in step 5 are anhydrous ethanol and deionized water, the drying temperature is 40 to 60° C., and the drying time is 24 to 48 hours.

Citation Information

Cited By

  • Cathode protection film based on COF material and preparation method and application thereof

    CN122417890A